Combined brachial plexus and vascular injury in the absence of bony injury. Issue 5 (1st September 2000) - MacNamara, A F; Ismail, A
Abstract : Neurovascular injury to the axillary vessels is well described in association with fracture or dislocation involving the shoulder joint or the humerus. Such injury however can also occur in the absence of bony injury. A case is presented of damage to the axillary artery and brachial plexus following blunt trauma. This case demonstrates that complex neurovascular damage can occur in the absence of fracture or dislocation. The importance of a thorough clinical assessment is highlighted and priorities with regard to diagnosis and management are discussed.